Inovasi Pembukuan Keuangan Secara Digital pada UMKM Jahit Melalui Aplikasi BukuKas di Ngawi - Anggraini, Yulia; Prastika Wafik Azizah (Amaluna: Jurnal Pengabdian Masyarakat, 2022)
Hidayah Sewing House (Rumah Jahit Hidayah) is a Micro Small and Medium Enterprises (SMEs) which is a services industry. The location of SMEs is in Mojomanis Village, Kwadungan District, Ngawi Regency and has been running since 2012. Hidayah Sewing House continues to grow and experience significant additional consumers. So that it can help the family economy during the Covid-19 Pandemic. But besides that, these SMEs still have not implemented an important process in a business, namely the process of financial bookkeeping. Therefore, it is important to have training to implement the financial bookkeeping process. To be efficient and in line with technological developments, financial records can be made digitally through the BukuKas application. This training activity aims to make it easier for SMEs actors to record their financial statements. The method used is ABCD, to find out the assets owned by the community and optimize them into an empowered program. The results obtained are that the financial training activities carried out have succeeded in helping Sewing SMEs in Mojomanis Village to carry out the financial bookkeeping process for their business easily, effectively, and efficiently.